Efficacy of Acupuncture Combined with Patient-Controlled Analgesia in the Treatment of Acute Pain after Back Surgery: A Meta-Analysis - Daling Deng; Feng Xu; Yafeng Wang; Lulin Ma; Tianhao Zhang; Wenjing Zhao; Xiangdong Chen (Pain Research and Management)
Objectives. Acupuncture is used worldwide to relieve both acute and chronic pain. Patient-controlled analgesia (PCA) is also frequently used for postoperative pain relief. However, there are few meta-analyses of the efficacy of acupuncture with PCA in reducing acute postoperative pain. This meta-analysis aimed to assess the effectiveness of acupuncture with PCA in relieving acute pain after back surgery. Methods. We searched seven databases (Cochrane Library, Web of Science, PubMed, China National Knowledge Infrastructure (CNKI), Wanfang database, Chongqing VIP (VIP), and Chinese BioMedical Literature Database (CBM)-from 1949 until now) without language restrictions for randomized controlled trials, including patients undergoing back surgery and receiving PCA alone or treated with acupuncture/sham acupuncture + PCA for pain relief. This meta-analysis assessed pain intensity, with visual analogue scale (VAS) score and postoperative opioid dosage as primary outcomes. Results. A total of 12 randomized controlled trials (n = 904) met the inclusion criteria. Compared with the control group (standard mean difference (SMD) = ‒0.42, 95% CI = ‒0.60 to ‒0.25, P<0.01) or sham acupuncture + PCA (SMD = ‒0.7, 95% CI = ‒0.94 to ‒0.46, P<0.01), acupuncture + PCA treatment reduced the VAS score in patients after back surgery. Acupuncture + PCA decreased the use of opioids after surgery compared to sham acupuncture + PCA (SMD = −0.35, 95% CI = ‒0.63 to ‒0.07, P=0.01) or control group (SMD = ‒0.82, 95% CI = ‒1.03 to ‒0.61, P<0.01). Furthermore, the use of acupuncture with PCA reduced the incidence of postoperative PCA-related total complications (odds ratio = 0.44, 95% CI = 0.23 to 0.85, P=0.01), but may not reduce the incidence of postoperative nausea and vomiting (odds ratio =0.82 , 95% CI =0.49 to 1.36, P=0.44). Conclusion. This systematic review found that acupuncture with PCA relieved acute pain after back surgery more effectively than PCA alone and could reduce opioid use and the incidence of postoperative PCA-related total complications